Kajian Awal Adosrben Abu Kayu Terhadap Methylene Blue - HR, Yuliani; Tri, Hartono; S, Puspita; Juliati, Juliati; A.A, Musfirah; A.N.P.Z, Isma; A.I, Ida (Politeknik Negeri Ujung Pandang, 2019)
This study aim the adsorption capacity of wood ash adsorbent from Makassar coto wood (ACM) and wood ash in the air cooking (AMA) of the blue methylene solution and its characteristics. ACM is activated by NaOH 3M and NaCl 0.85 M, to improve its performance as an adsorbent. ACM without permission and activation as well as AMA of 0.25 grams were tested against 50 ml of methyl blue with concentrations of 10, 20, 30, 40 and 50 ppm. Adsorption runs for 1.5 hours using a shaker at a speed of 500 rom. Adsorbent and adsorbate use filter paper then the absorbance of the filtrate is taken to determine the equilibrium concentration (Ce) of methylene blue. The maximum adsorbent capacity (qm) is determined using the Langmuer equation for the administrator's ACM adorbent type and without activation with AMA. Other tests consisted of adsorbent characteristics consisting of ACM and AMA compositions. The results of the study showed differences, namely ACA having a composition of 28.15% Silica (Si), 20.86% Ca and AMA namely 30.68% Si, 15.29% Ca. The maximum adsorption capacity (qm) of ACM is 12.37 mg / g and for AMA is 10.29 mg / g. Activation of 3M NaOH ACM has an adsorption capacity (qm) of 13.01 mg / g and activation of 0.85 M NaCl which is 15.15 mg / g.